Predictors of smoking abstinence among diabetic smokers: Evidence from the French national smoking cessation registry CDTnet - Ingrid Allagbé; David Baudoin; Bastien Rance; Anne-Laurence Le Faou (PLoS ONE, 2025)
Evidence suggests that diabetic smokers are less likely to quit smoking when compared to non-diabetic smokers. This study aimed to determine predictors of abstinence among diabetic smokers attending smoking cessation services (SCSs) across France. We analysed data from 94,827 adult smokers registered in the French national smoking cessation registry (CDTnet) between 2007 and 2016. Participants attended ≥2 SCS visits, and one-month continued abstinence was confirmed by carbon monoxide measurement. Among 6,405 diabetic smokers, 33% achieved one-month continued abstinence, versus 38% among 88,422 non-diabetic smokers (p < 0.001). Positive predictors of abstinence among diabetic smokers included employment (odds ratio [OR], 1.61; 95% confidence interval [CI], 1.37–1.89), ≥ 3 prior quit attempts (OR, 1.61; 95% CI, 1.36–1.91), low nicotine dependence (OR, 1.42; 95% CI, 1.13–1.78), prescription of combined nicotine replacement therapy (NRT) (OR, 1.43; 95% CI, 1.19–1.72) or varenicline (OR, 1.64; 95% CI, 1.20–2.25), and ≥7 SCS consultations (OR, 4.47; 95% CI, 3.40–5.84). Conversely, negative predictors included history of myocardial infarction/angina (OR, 0.82; 95% CI, 0.70–0.96), chronic bronchitis/chronic obstructive pulmonary disease (OR, 0.79; 95% CI, 0.69–0.91), anxiety (OR, 0.82; 95% CI, 0.71–0.94), recent cannabis use (OR, 0.67; 95% CI, 0.50–0.90), and exclusive oral NRT use (OR, 0.70; 95% CI, 0.56–0.88). Overall, tailored cessation programs are crucial for enhancing cessation outcomes among diabetic smokers.